qu'es ce l’épigénétique et quels en sont les impacts sur la production laitière - SLIMANI, Romaissa (My University, 2022)
This study analyzes the effect of epigenetic essentially mastitis and undernourishment and milking frequency on milk production, the quantity point of view in a farm located in the AIN DEFLA region. The research concerned the milk production followed by 13 dairy cows of the Montbeliarde breed which has the same age and stage of lactation and J body weight that approaches. The results showed that the factors studied (epigenetic monofraite under power and mastitis) significantly affects the average daily milk production. The epigenetic marks are involved in the expression of genetic potential (phenotype) are heritable, changeable depending on the environment, and reversible with consequences more or less long term as their paramount importance in breeding.
Keywords: epigenetic; mastitis; milking frequency; undernourishment dairy cow